Joint Bidding in Infrastructure Procurement - Estache, Antonio; Iimi, Atsushi (World Bank, Washington, DC, 2012)
To utilize public resources efficiently, it is required to take full advantage of competition in public procurement auctions. Joint bidding practices are one of the possible ways of facilitating auction competition. In theory, there are pros and cons. It may enable firms to pool their financial and experiential resources and remove barriers to entry. On the other hand, it may reduce the degree of competition and can be used as a cover for collusive behavior. The paper empirically addresses whether joint bidding is pro- or anti-competitive in Official Development Assistance procurement auctions for infrastructure projects. It reveals the possible risk of relying too much on a foreign bidding coalition and may suggest the necessity of overseeing it. The data reveal no strong evidence that joint bidding practices are compatible with competition policy, except for a few cases. In road procurements, coalitional bidding involving both local and foreign firms has been found pro-competitive. In the water and sewage sector, local joint bidding may be useful to draw out better offers from potential contractors. Joint bidding composed of only foreign companies is mostly considered anti-competitive.